Repigmentation of cutaneous scars depends on original wound type. Issue 1 (14th May 2013) - Chadwick, Sarah L.; Yip, Christina; Ferguson, Mark W. J.; Shah, Mamta
Abstract Cutaneous scarring is currently an inevitable outcome following skin injury. Abnormal pigmentation within scars makes them more noticeable, causing distress for patients, particularly as there is no reliable and effective treatment available to date. The Duroc pig, known to scar badly, was used to investigate repigmentation of scars resulting from three different wound types: incisional, partial thickness excisional and full thickness excisional. Wounds were created on the backs of Duroc pigs and the resulting scars harvested at days 35, 56, 70 and 90 days post‐injury. Scars were processed for histology and immunohistochemistry, quantitatively analysed using image analysis software and subjected to statistical analysis. Photographs of the macroscopic appearance of scars were scored for pigmentation using a visual analogue scale. Results demonstrated temporal and spatial differences in melanocyte repopulation and function within scars from different wound types. The microscopic pigment deposition did not correlate with macroscopic appearances in mature scars. Pigmentation of scars is dependent on the width and depth of wounds. This study has provided important information on which we can base future studies to investigate factors controlling the repigmentation of scars.